The effect of high fat diet on M Cells and tight junction proteins of Intestinal Mucosa of rats / Auni Aqilah Zainal Abidin - Zainal Abidin, Auni Aqilah (2016)
M cells and intestinal tight junction proteins (TJPs) are important components of intestinal barrier which is compromised by high fat diet (HFD). Objective of this study was to determine the effect of HFD on M cells and TJPs of intestinal mucosa of rats. Four weeks old, twenty male Wistar rats were divided into control (n=10) and HFD (n=10) groups. After 6 weeks, ileum segments with Peyer’s patches (PP) and feces were collected. Immunohistochemical staining and fecal calprotectin (FCP) level was measured. M cell expression in the PP (1.125 ± 0.354 vs 2.3 ± 0.675, p = 0.004) and villi (1.625 ± 0.518 vs 2.3 ± 0.458, p= 0.045) were significantly higher in HFD group than the control. Claudin-3 expression in the PP and villi was not different significantly between the two groups. Claudin-4 expression in the PP (2.1 ± 0.583 vs 1.6 ± 0.669, p = 0.018) and villi (1.975 ± 0.670 vs 1.55 ± 0.597, p = 0.015) was significantly decreased in HFD group than the control. Occludin expression in the PP of HFD group was significantly decreased compared to the control group (2.0 ± 0. 633 vs 1.2 ± 0.4, p = 0.001) but was not significantly decreased in the villi. FCP in HFD group was significantly higher compared to the control (40.172 ± 4.0852 vs 49.058 ± 1.174, p = 0.016). HFD for 6 weeks caused increased M cell expression and reduced claudin-4 and occludin expressions in male Wistar rats which were associated with intestinal inflammation.